Physiological synchronization in the clinical process: a research primer - Kleinbub, Johann R.; Talia, Alessandro; Palmieri, Arianna (Journal of counseling psychology, 2020)
Physiological synchronization is the study of how individuals in interaction coregulate their physiology. The topic has sparked increasing interest in counseling and psychotherapy research, where it has been found to be associated with the therapeutic alliance, clinicians' empathy and patients' outcome. Physiological synchronization allows researcher to investigate subtle but fundamental aspects of the clinical process through objective measures. In this article, we aim to offer a guide to researchers and clinicians to explore this growing field of study. We begin by reviewing the existing literature of physiological synchronization in clinical relationships, and then we provide practical guidelines for research. We discuss the various aspects involved in synchronization studies: study design, selection of physiological signals, data analytic approaches, and interpretation of results. To better illustrate how to implement these types of design, we provide a running example describing the data collection and analysis of a single-case study. In the example we discuss both how to conduct a longitudinal nomothetic analysis, as well as a moment-to-moment idiographic exploration of the clinical content. In this latter analysis, in particular, we show how physiological synchronization can be used in combination with 2 transcripts analysis tools, the Patient Attachment Coding System, and the Therapist Attunement Scales to reach a deeper understanding of the ongoing processes. We conclude by arguing that research in counseling and psychotherapy has much to gain from and contribute to the overall development of our understanding of physiological synchronization in human interaction.